Self-adaptive algorithms for the split problem of the demicontractive operators. (2nd September 2018) - Yao, Yonghong; Liou, Yeong-Cheng; Postolache, Mihai
Abstract : Self-adaptive algorithms are presented for solving the split common fixed point problem of demicontractive operators in Hilbert spaces. Weak and strong convergence theorems are given under some mild assumptions.